1992
DOI: 10.1093/tropej/38.6.307
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine functions in Sickle Cell Anaemia Patients

Abstract: In this study, 80 male and female sickle cell patients, aged 4-50 years, with mild (severity index, SI < 6) and severe (SI > or = 6) forms of the disease were investigated). The levels of luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone, cortisol, growth hormone (GH), free thyroxine (T4), and free triiodothyronine (T3) were determined. The results were evaluated and the mean +/- 2 SD values were compared with those obtained in age- and sex-matched normal controls. The findings indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 0 publications
2
38
0
1
Order By: Relevance
“…86 In 80 Saudi patients with sickle cell anaemia, hormonal assay showed normal levels of T3, T4 and growth hormone, low levels of cortisol, testosterone and LH, and variable changes in FSH. 87 These abnormalities occurred more frequently in the patients with severe disease. Studies of thyroid function have shown that blood levels of thyroxine, thyroxine-binding capacity and the free thyroxine index were not significantly different in 90 SS children (1-15 yrs) than in AS and AA controls.…”
Section: Endocrine Dysfunction and Growth Retardationmentioning
confidence: 94%
“…86 In 80 Saudi patients with sickle cell anaemia, hormonal assay showed normal levels of T3, T4 and growth hormone, low levels of cortisol, testosterone and LH, and variable changes in FSH. 87 These abnormalities occurred more frequently in the patients with severe disease. Studies of thyroid function have shown that blood levels of thyroxine, thyroxine-binding capacity and the free thyroxine index were not significantly different in 90 SS children (1-15 yrs) than in AS and AA controls.…”
Section: Endocrine Dysfunction and Growth Retardationmentioning
confidence: 94%
“…4 Possible underlying pathophysiologic mechanisms of hypogonadism include disruptions in the hypothalamic-pituitary-gonadal axis leading to primary testicular failure. However, studies are inconsistent as to whether primary testicular failure 5,6 or secondary hypothalamic-pituitary dysfunction 3,4,[7][8][9] is the cause. A recent report found low serum testosterone levels in 8 of 34 men with SCD and all 8 had low FSH and LH levels, suggesting a central mechanism.…”
Section: Fertility In Menmentioning
confidence: 99%
“…8 Finally, 72 to 100% of the patients with sickle cell disease had an impairment of at least one sperm parameter. Patients with sickle cell disease often have moderate to severe hypogonadism, [9][10][11] of unknown origin, although several mechanisms have been suggested: primary hypogonadism, 9,12 hypogonadism induced by repeated testicular infarction, 13 zinc deficiency, 14,15 and puberty delay due to span-height retardation. [16][17][18] Hydroxyurea itself has been reported to impair spermatogenesis in mammals, resulting in testicular atrophy, 19-21 a reversible decrease in sperm count, [19][20][21][22][23] and abnormal sperm morphology 20,24 and motility.…”
Section: Introductionmentioning
confidence: 99%